Ketergantungan Energi Dan Posisi Politik Hungaria Dalam Penolakan Sanksi Uni Eropa Terhadap Rusia - Marpaung, Ayu Yosefina; Arthadeswa, Hafiza Adeylie Chantika (Jurnal Ilmiah Hubungan Internasional Fajar, 2025)
The European Union has imposed a series of sanctions on Russia in response to various actions deemed to violate international law and threaten regional stability. However, amid the EU's efforts to maintain unity in facing Russian aggression, Hungary has taken a different stance. Under the leadership of Prime Minister Viktor Orbán, Hungary has consistently opposed several EU sanctions against Russia and maintained economic and energy relations with Moscow. This stance not only creates tensions within the EU but also sparks criticism regarding Hungary's commitment to European solidarity. The aim of this study is to analyze the factors behind Hungary's opposition of EU sanctions against Russia. This research employs a qualitative method with a literature review approach. Data is collected from various sources such as books, academic journals, newspapers, and official documents. The results show that Hungary oppose the EU's sanctions against Russia due to its high dependence on Russian gas, oil, and nuclear energy in order to maintain economic stability and energy security. This stance provides short-term economic benefits but also creates tensions with the EU. Hungary's close relationship with Russia strengthens its position within the EU but also weakens the effectiveness of sanctions against Moscow. Keywords: European Union, Hungary, Russia, Dependency Theory